Principles of synthesis of logic and linguistic models of natural language sentences - Вавіленкова, А. І. (Science-based technologies, 2017)
The paper formulates the basic problem of the content automatic processing of textual information. An author describe formal rules by which we can found logical connections between natural language sentences that compose the electronic text document. Principles of synthesis of logic and linguistic models (LLM) are the conditions under which, within LLM, we can replace components identical by content and form one-dimensional arrays, elements of which are words or phrases that connect natural language sentences to each other in text’s parts. The above principles can be applied to text’s sentences, which are arranged sequential, as well as for sentences from several paragraphs. Expansion and improvement of principles of synthesis for various methods of logical connection between the parts of the text will improve the search content quality using formal logic and linguistic models.